Ácidos graxos e colesterol da carne de cordeiros confinados recebendo dietas contendo fontes lipídicas e submetidos à restrição e realimentação - Homem, Antonio Carlos; Ezequie, Jane Maria Bertocco [UNESP]; Rodrigues, Daniela Junqueira [UNESP]; Pinheiro, Rafael Silvio Bonilha [UNESP] (FapUNIFESP (SciELO), 2015)
It was evaluated the effects of sunflower grains inclusion or protected fat in the diet and compensatory growth on the loin eye area, subcutaneous fat thickness, chemical composition, cholesterol concentration and fatty acid composition of intramuscular fat of Longissimus lumborum of lambs distributed in a completely randomized design in factorial scheme (3 diets x 2 feeding management). Intramuscular cholesterol from lambs fed with diet containing protected fat (28.5mg 100g-1) was lower (P<0.05) than that of the control (36.8mg 100g-1) and sunflower grains (38.1mg 100g-1). The restriction and refeeding didn’t cause change (P>0.05) in the fatty acids profile, but diet containing sunflower grains increased polyunsaturated/saturated ratio due to(P<0.05) the superiority of 20% in the proportion of polyunsaturated, reflecting directly the increase in linoleic acid. Inclusion of lipid sources in the diet of feedlot sheep is a tool that helps to improve the quality of intramuscular fat of lambs, whereas the protected fat reduces cholesterol and sunflower grains elevates the concentration of polyunsaturated fatty acids. Feeding restriction and refeeding period does not alter the chemical composition and quality of intramuscular fat.
Fatty acids and cholesterol of meat from lambs fed diets containing lipid sources and subjected to restriction and refeeding
Keywords: Chemical composition; Conjugated linoleic acid; Fat thickness; Protected fat; Sunflower grains